Probiotics in Women and Pediatrics Health; A Narrative Review - Wassan Nori; Nabeeha Najatee Akram; Methaq Mueen Al-kaabi (Al-Anbar Medical Journal)
Probiotic use to improve health is not new; but recently, it has attracted much attention concerning human health and diseases. The human gut is a delicate ecosystem where bacteria and host cells interact with each other. This is an important part of gut homeostasis and human development.  Disruption of this sensitive ecosystem may have detrimental health repercussions linked to impaired gut microbiota (GM). GM were extensively examined as an underlying mechanism for disease development and progression. Additionally, it was used as a tailored method for preventing and treating disease. Because of the strong association between GM, health, and disease, there has been much interest in employing probiotics or living microorganisms, to regulate GM to prevent or cure specific diseases. Herein, probiotics' role in enhancing women's and pediatric well-being was addressed as a marker of disease and as therapeutic avenues; where we discussed probiotics indications, efficacy, safety profiles, and future prospects in clinical practice.